Cluster Lensing And supernova Survey with Hubble (CLASH): an overview - Postman, Marc; Zitrin, Adi; Bartelmann, Matthias; Meneghetti, Massimo (The astrophysical journal. Supplement series, 2012)
The Cluster Lensing And Supernova survey with Hubble (CLASH) is a 524-orbit multi-cycle treasury program to use the gravitational lensing properties of 25 galaxy clusters to accurately constrain their mass distributions. The survey, described in detail in this paper, will definitively establish the degree of concentration of dark matter in the cluster cores, a key prediction of CDM. The CLASH cluster sample is larger and less biased than current samples of space-based imaging studies of clusters to similar depth, as we have minimized lensing-based selection that favors systems with overly dense cores. Specifically, twenty CLASH clusters are solely X-ray selected. The X-ray selected clusters are massive (kT > 5 keV; 5 - 30 x 10^14 M_solar) and, in most cases, dynamically relaxed. Five additional clusters are included for their lensing strength (Einstein radii > 35 arcsec at z_source = 2) to further quantify the lensing bias on concentration, to yield high resolution dark matter maps, and to optimize the likelihood of finding highly magnified high-redshift (z > 7) galaxies. The high magnification, in some cases, provides angular resolutions unobtainable with any current UVOIR facility and can yield z > 7 candidates bright enough for spectroscopic follow-up. A total of 16 broadband filters, spanning the near-UV to near-IR, are employed for each 20-orbit campaign on each cluster. These data are used to measure precise (sigma_phz < 0.02(1+z)) photometric redshifts for dozens of newly discovered multiply-lensed images per cluster. Observations of each cluster are spread over 8 epochs to enable a search, primarily in the parallel fields, for Type Ia supernovae at z > 1 to improve constraints on the time dependence of the dark energy equation of state and the evolution of such supernovae in an epoch when the universe is matter dominated.
Gesehen am 21.09.2017